The potential role of taxes and subsidies on food in the prevention of obesity in Europe (2009)
ABSTRACT: Background Obesity implies costs not only for the individual but also for society. The authors explore the opinions of stakeholders on the potential of taxes or subsidies, as measures for tackling obesity in Europe. Methods Structured interviews were conducted using Multicriteria Mapping, a computer-based, decision-support tool, with 189 interviewees drawn from 21 different stakeholder categories across nine members of the EU interviews, to appraise 20 predefined policy options aimed at reducing obesity, including ‘taxing obesity-promoting foods’ and ‘subsidising healthy foods.’ A four-step approach involved selecting options, defining criteria, scoring options quantitatively and weighting criteria to provide overall rankings of options. Interviews were recorded and transcribed to yield qualitative data. Results Compared with other policy options appraised, taxation and subsidies were not favourably received, mainly because they were considered difficult to implement. Overall, trade unions rated both options more favourably than all other stakeholder groups. As anticipated, both options received their lowest scores from representatives of the farming, food processing and advertising industries. Nutritional/obesity advisory experts and public sector caterers gave the most positive ratings to subsidies overall. Along with public health professionals, large commercial retailers were most in favour of taxation. Conclusions Taxation and subsidies were poorly appraised compared with other policy measures, with stakeholders expressing reservations mainly focussed on the practicalities and cost of introducing such measures. Although applying taxes/subsidies could be useful to combat obesity, the study suggests that most stakeholders still need to be convinced of their viability and acceptability when compared with other measures.